(untitled) (Proceedings of the International Conference on Future of Women, 2019)
This paper examines the phenomenon of human trafficking in Sri Lanka, a nation uniquely situated as an origin, transit and destination country for men, women and children trafficked for forced labour, and sexual exploitation. Sex trafficking is a type of human trafficking that disproportionately affects girls and women. Every year children, women and men become trafficking victims either in their own countries or foreign countries. The practice gravely violates human rights and is considered a transnational organized crime. Almost every country of the world is affected by human trafficking, as source, countries of transit or destinations or even combination of all the three. Often less developed countries serve as sources while more developed countries serve as destinations. This paper is the reflection of my experience at International Organization for Migration (IOM) on a counter trafficking project where the first international human trafficking case filed before the High court of Colombo and where all 3 traffickers were convicted. In Part II, I will illustrate the complexity of understanding trafficking in its full social context using the testimony of the victims I encountered during my tenure at IOM. In Part III, I will discuss control methods used against the two victims of this human trafficking case for sexual exploitation. The paper ultimately concludes that broader, victim based initiatives are necessary both to assist victims and provide a firmer basis for future trafficking prosecutions.